Optimized Design of Bio-Inspired Wind Turbine Blades - Dai, Yuanjun; Wang, Dong; Liu, Xiongfei; Wu, Weimin (Fluid dynamics & materials processing, 2024)
To enhance the aerodynamic performance of wind turbine blades, this study proposes the adoption of a bionic airfoil inspired by the aerodynamic shape of an eagle. Based on the blade element theory, a non-uniform extraction method of blade elements is employed for the optimization design of the considered wind turbine blades. Moreover, Computational Fluid Dynamics (CFD) is used to determine the aerodynamic performances of the eagle airfoil and a NACA2412 airfoil, thereby demonstrating the superior aerodynamic performance of the former. Finally, a mathematical model for optimizing the design of wind turbine blades is introduced and a comparative analysis is conducted with respect to the aerodynamic performances of blades designed using a uniform extraction approach. It is found that the blades designed using non-uniform extraction exhibit better aerodynamic performance.